The role of inflammatory mediators in renal vascular remodeling in patients with arterial hypertension - E. S. Krutikov; S. I. Chistyakova (Кубанский научный медицинский вестник)
The relationship between level of pro-inflammatory cytokines and processes of remodeling of intra-renal vessels in patients with essential arterial hypertension (EAH) were studied. Were surveyed 80 patients with EAH. Ambulatory blood pressure monitoring and renal artery doppler ultrasound were performed all patients. Further we determined the level of IL-1, IL-6, TNF-α. It was found that patients with EAH and overweight, there are more significant changes in circadian blood pressure profile and renal hemodynamics. Significant correlation between IL-6, TNF-α and indicators of the remodeling intra-renal vessels were identified. It may indicate that processes of nonspecific inflammation causes the structural alteration of the renal vascular in the patients with EAH.